A novel visual brain-computer interfaces paradigm based on evoked related potentials evoked by weak and small number of stimuli - Xiao, Xiaolin; Gao, Runyuan; Zhou, Xiaoyu; Yi, Weibo; Xu, Fangzhou; Wang, Kun; Xu, Minpeng; Ming, Dong (Frontiers in Neuroscience, 2023)
Traditional v-BCIs usually use large-size stimuli to attract more attention from users and then elicit more distinct and robust EEG features, which would cause visual fatigue and limit the length of use of the system. On the contrary, small-size stimuli multiple and repeated stimuli code more instructions and increase separability among each code. These common v-BCIs paradigms can cause problems such as redundant coding, long calibration time, and visual fatigue. To address these problems, this study presents a novel v-BCI paradigm using a weak and small amount of stimuli accomplishing nine instructions controlling with only three very small stimuli, which are located between instructions with eccentricities subtended 0.4° and flashed in the row-column paradigm. The weak stimuli around each instruction would evoke specific ERPs, and a template-matching method based on Discriminative Spatial Patterns (DSPs) was employed to recognize these features containing the intention of users. Nine subjects participated in the offline and online experiments using this novel paradigm. The average accuracy of the offline experiment was 93.46% and the online average information transfer rate (ITR) was 120.95 bits/min. Notably, the highest online ITR could achieve at 177 bits/min. These results demonstrate the feasibility of using a small and small number of stimuli to implement a friendly v-BCI. Furthermore, the proposed novel paradigm achieved higher ITR than traditional ones using ERPs as the controlled signal, which showed its great potential of being widely used in various fields.